2023
DOI: 10.1093/ofid/ofad561
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Recurrence of Community-Onset Urinary Tract Infections Caused by Extended-Spectrum Cephalosporin-Resistant Enterobacterales

Helen L Zhang,
Reinaldo Perez,
Jay Krishnan
et al.

Abstract: Background Extended spectrum cephalosporin-resistant Enterobacterales (ESCrE) are an increasingly important cause of community-onset urinary tract infections (UTIs), including recurrent infections. We evaluated risk factors for recurrence among patients with community-onset ESCrE UTI. Methods This retrospective cohort study included adults with community-onset ESCrE UTI in Duke University Health System from April 2018 through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…A larger sample size from the 2016 national Healthcare-Associated Infections prevalence survey in the UK found that the percentage of OAT overuse was 62.5% [50]. Therefore, it appears that non-compliance with professional society guidelines and AMS for cystitis are the likely major contributors to AMR [15,40,41], but other factors may also be involved, so further investigation is warranted.…”
Section: Contribution Of Urinary Tract Infections (Utis) To Amrmentioning
confidence: 99%
See 4 more Smart Citations
“…A larger sample size from the 2016 national Healthcare-Associated Infections prevalence survey in the UK found that the percentage of OAT overuse was 62.5% [50]. Therefore, it appears that non-compliance with professional society guidelines and AMS for cystitis are the likely major contributors to AMR [15,40,41], but other factors may also be involved, so further investigation is warranted.…”
Section: Contribution Of Urinary Tract Infections (Utis) To Amrmentioning
confidence: 99%
“…A history of two or more episodes of bacterial cystitis is an independent risk factor [15,79] for recurrent cystitis, defined as ≥2 episodes in 6 months or ≥3 in a year. Compared to men, the higher incidence of cystitis in women is generally linked to their shorter urethra and infrequent voiding [69] that thins the urothelial barrier [12,62,80] for the proximal seeding of uropathogens from the adjacent cavities of the vagina and anus [81].…”
Section: Cystitis Etiology and Treatmentmentioning
confidence: 99%
See 3 more Smart Citations